Investigations of Dynamic Mechanical Performance of Rubber Concrete under Freeze-Thaw Cycle Damage - Zhang, Jingli (Shock and Vibration, 2023)
In order to study the effect of the freeze-thaw cycle on the integrity and dynamic mechanical performance of rubber concrete, the wave speed of rubber concrete specimens with 10% rubber volume was measured by a nonmetallic ultrasonic detector. The impact tests were also performed on rubber concrete specimens with different numbers of freeze-thaw cycles (0, 25, 50, 75, 100, and 125) at different impact air pressures (0.3, 0.4, 0.5, and 0.6 MPa) using a 74 mm diameter split Hopkinson pressure bar (SHPB) device, peak stress, ultimate strain dynamic intensity enhancement factor (DIF), and energy absorption effect. The results show that with the increase of freeze-thaw cycles, the wave speed decreases, and the freeze-thaw action will damage the rubber concrete and reduce the longitudinal wave velocity. Under the same freeze-thaw cycles, with the rise of strain rate, the peak stress, limit strain, DIF, and absorbed energy increase, and there is an obvious strain rate effect; under the pressure of 0.6 MPa, the peak stress of 25, 50, 75, 100, and 125 freeze-thaw cycles decreases by 25.1%, 37.1%, 46%, 52.5%, and 54.8%. With the increase of the freeze-thaw cycles, the peak stress of the specimen decreases, and the decrease gradually decreases. After the number of cycles exceeds 100, the stress decrease of the specimen is no longer obvious, the limit strain increases, and the absorbed energy decreases. The freeze-thaw environment significantly reduces the strength and integrity of rubber concrete specimens.